Effect of temperature and storage time on the amount of bacteria content and physical quality of se'i pork in Kefamenanu City, North Central Timor Regency - Pricila Aquilla Bifel; Lukas Pardosi; Gergonius Fallo; I Gede Arya Wiguna (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Pork se'i meat is a special product from East Nusa, which is processed by smoking it using wood. However, temperature conditions and storage time can affect the quality of pork se'i meat. This study aims to determine the effect of temperature and storage time on the bacterial content and the physical quality of pork se'i. The research sample was taken from the Se'i Babi production depot in Kefamenanu City. This study used a factorial Completely Randomized Design (CRD). The temperature factor was 3 treatments, namely 27°C, 32°C, and 37°C, while the storage time factor was 3 treatments, namely 1 day, 2 days, and 3 days. Observation of bacterial content with the Total Plate Count (TPC) test, and observation of the physical quality of the se'i with the organoleptic test. Data analysis is descriptive and quantitative. The results showed that temperature and storage time affected the amount of bacterial content and physical quality of pork se'i, where a good temperature for storing pork se'i was 32°C. The lowest average bacterial growth was 146.6 cfu/g, 120 cfu/g, and 156.6 cfu/g, and the lowest average organoleptic value is at 32°C, and the highest is at 27°C. For making pork se'i so that in the future we can pay more attention to processing methods because in the future pork se'i will increasingly become a favorite food in society.